Penerapan Gaya Bohemian pada Interior La Luna Resort di Yogyakarta (Kajian Estetik) - Rizky Hikmatul Maulidia; Ersnathan Budi Prasetya (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
The La Luna is one of the resort hotels located on Jalan Palagan Tentara Pelajar No.km.8 Ngaglik District, Sleman Regency. La Luna applies a bohemian interior style and cottage inn concept. The bohemian style that is applied to La Luna is used as branding for this resort so that this place is known as a unique, aesthetic and instagrameable inn. The purpose of this study was to find out how the application of bohemian style and aesthetic value to the interior of La Luna Resort in Yogyakarta. This study uses a qualitative research method with a bohemian and semiotic interior approach to seek aesthetic value. Sources of data obtained from field observations and interviews. The results of the study show an analysis of the bohemian style at La Luna Resort with some literature on bohemian origin culture and examines the aesthetic values of the interior as well as the new finding that the bohemian interior that has been known to be a capitalized element. It is hoped that this analysis can appreciate the interior with a bohemian style along with the aesthetic value based on the bohemian cultural history contained therein.